Application Of The Concept Of Singular Value Decomposition For The Making Of Watermark In Documents - Sinar Sinurat; Edward R Siagian (Bahasa Indonesia, 2022)
Watermark is a part of steganography that is used by many users in electronic and non-electronic documents. Watermark certainly does not guarantee the safe use or modification of the document, but only the legitimacy of ownership of the document. Watermarking is a part of steganography that is used by many users in electronic and non-electronic documents. Watermarking certainly does not guarantee the safe use or modification of the document, but only the legitimacy of ownership of the document. Establishing a digital watermark will improve the owner's document security. Hiding a label by inserting datum bits in the image segment using Singular Value Decomposition (SVD), as a part of Watermarking. Watermark domains are digital documents in the form of videos, images, text, sound. Watermarking applications built by applying singular value decomposition to numbers